2019
DOI: 10.1108/qmr-02-2017-0059
|View full text |Cite
|
Sign up to set email alerts
|

Consumer engagement on social media: insights from a virtual brand community

Abstract: Purpose Based on the conceptual model of consumer engagement in a virtual brand community, this study aims to investigate this phenomenon and gauges the validity of the model’s assumptions in the context of a Facebook fan page. Design/methodology/approach The interactions between L’Oréal Paris Brazil and the members of its virtual community were collected for three months using a netnographic approach. The data of these interactions were evaluated using content analysis techniques. Findings The dimensions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 73 publications
1
38
0
1
Order By: Relevance
“…A study reported that the Covid-19 pandemic increased panic buying for some consumption categories but also decreased consumption for the hospitality industry (Hall et al , 2020). Many marketing-related studies have described the importance of social media for social communication, social networks, social influence (Treviño and Pineda Garelli, 2019; Mazzoli et al , 2019; Hallock et al , 2019), customer engagement (Lima et al , 2019), negative information, false claims, social sharing, praise or revenge (Tuten and Perotti, 2019; Whiting et al , 2019), but these studies did not provide an understanding of how social media can play an important role in raising insecurities about visiting retail stores for necessities of life, health risks, perceived risk and social proof which increased stockpiling behaviour. Therefore, the present study aims to address this gap by exploring the role of social media to generate social proof in an engaged society for stockpiling behaviour of customers during Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that the Covid-19 pandemic increased panic buying for some consumption categories but also decreased consumption for the hospitality industry (Hall et al , 2020). Many marketing-related studies have described the importance of social media for social communication, social networks, social influence (Treviño and Pineda Garelli, 2019; Mazzoli et al , 2019; Hallock et al , 2019), customer engagement (Lima et al , 2019), negative information, false claims, social sharing, praise or revenge (Tuten and Perotti, 2019; Whiting et al , 2019), but these studies did not provide an understanding of how social media can play an important role in raising insecurities about visiting retail stores for necessities of life, health risks, perceived risk and social proof which increased stockpiling behaviour. Therefore, the present study aims to address this gap by exploring the role of social media to generate social proof in an engaged society for stockpiling behaviour of customers during Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the authors articulated the consumers' online brand-related activities framework, comprising the three aforementioned acts in a hierarchically ordered fashion. However, their behaviourally-oriented model that rests on the psychological paradigm as theoretical underpinning conceptualizes CBE as a multidimensional phenomenon comprising cognitive, emotional and behavioural aspects (Moura et al, 2019) without attending to actual SMBCs data. From a CMDA point of view, multidimensionality is rather approached as the discursive performance of concurrent layers of attribution, based on identifiable brand knowledge structure dimensions, namely attributes, consumer benefits and attitudes (Keller, 1998).…”
Section: From Valencing To Valorizationmentioning
confidence: 99%
“…Social networks on the internet are viable through digital platforms known as social media (Jain et al , 2018; Tsimonis and Dimitriadis, 2014). Companies, such as sports clubs, can promote products and services through word-of-mouth, by which consumers transmit informal opinions, criticisms and suggestions about them (Lima et al , 2019; Kozinets et al , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%